2017
DOI: 10.1039/c7cs00418d
|View full text |Cite
|
Sign up to set email alerts
|

Atomically thin non-layered nanomaterials for energy storage and conversion

Abstract: After the discovery of graphene, two-dimensional nanomaterials with atomic thickness and large lateral size have attracted tremendous research interest due to their high specific surface areas, exotic electronic structures, and fascinating physical and chemical properties. Even though recent studies are mainly focused on atomically thin nanomaterials with layered structures due to their easy preparation and characterization, the investigation of non-layered nanomaterials is also proceeding as new types of ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
146
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(146 citation statements)
references
References 148 publications
(241 reference statements)
0
146
0
Order By: Relevance
“…The resulting TMOs/CNF composite materials exhibited electrochemical performance in supercapacitors and electrocatalysis. It has been demonstrated that NiO/Co 3 O 4 NPs distributed in both internal and surface of CNF exhibit excellent electrochemical supercapacitive performances. Lou and co-workers prepared flexible films derived from electrospun CNF incorporated with Co 3 O 4 hollow NPs, as self-supported electrodes, which exhibited high specific capacitance and excellent cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting TMOs/CNF composite materials exhibited electrochemical performance in supercapacitors and electrocatalysis. It has been demonstrated that NiO/Co 3 O 4 NPs distributed in both internal and surface of CNF exhibit excellent electrochemical supercapacitive performances. Lou and co-workers prepared flexible films derived from electrospun CNF incorporated with Co 3 O 4 hollow NPs, as self-supported electrodes, which exhibited high specific capacitance and excellent cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…Rational design of nanostructured electrode nanomaterials, which possess the properties to enhance reaction kinetics, accommodate structural strains, facilitate rapid mass transport paths, and enlarge ion storage sites and interfaces, have been shown to be an exciting approach to boost the performance of energy storage devices . Unfortunately, some electrochemically favorable nanostructures lose their structural integrity during cycles and finally result in sluggish electrochemical reactions and rapid decay of capacity, particularly at high rates . Therefore, how to maintain structurally stable nanostructures with enhanced electrochemical performances is another research target for high‐rate energy storage devices …”
mentioning
confidence: 98%
“…It has been reported that 2D materials have demonstrated plenty of advantages compared to the corresponding bulk materials . In the honeycomb‐inspired microspheres, the basic constitutional nanostructures are 2D CoMoO x nanosheets.…”
mentioning
confidence: 99%
“…To take advantage of the intrinsic structures of different metal sulfides, two basic strategies, 'top-down' and 'bottom-up' methods, have been utilized to prepare ultrathin 2D-MSs. [95] The layered MSs have in-plane chemical bonds but weak outof-plane van der Waals bonds, which mean the dimension of the bulky MSs can be reduced as 2D materials. Therefore, the top-down method, such as mechanical exfoliation, liquid exfoliation, and chemical deposition, are able to easily produce single-or few-layer nanosheets from bulky MSs, such as MoS 2 , VS x , SnS 2 , and WS 2 .…”
Section: Synthetic Strategiesmentioning
confidence: 99%